Differentiation of hypoglycemic states according to their heterogeneity (review and personal observation) - Tykhonova, Tetiana; Barabash, Nadiya; Soldatenko, Inna (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
The article is dedicated to the problems of differentiated diagnostics of conditions, which are accompanied by the development of hypoglycemia. In clinical practice hypoglycemic syndrome usually associated with diabetes mellitus and considered as consequences of hypoglycemic treatment but causes of this conditions can be different. In the review possible causes of low blood sugar of endocrine and non-endocrine genesis are discussed, their pathogenetic mechanisms are explained.It is emphasized that often hypoglycemic states remain undiagnosed on the background of existing severe somatic pathology, while they can be the cause of deterioration, coma, and sometimes even death of the patient. Among the causes of hypoglycemic states of non-endocrine origin, malignant tumors occupy a special place, as illustrated by the clinical case from personal experience presented in the article.Analyzing this medical history, it should be noted that not always the diagnosis, which seemed obvious at first, is confirmed after a thorough examination of the patient. In addition, the genesis of hypoglycemic seizures often cannot be established as quickly as in our clinical case, especially in oncologic pathology. It may be due to the small size of the malignancy, difficult availability of the tumor for imaging by instrumental methods and other factors. Numerous diagnostic algorithms for determining the cause of hypoglycemic states have been described in the literature, but each of the following algorithms only complements the previous one, taking into account the results of new clinical trials. The article emphasizes that strict adherence to modern guidelines for the management of patients with hypoglycemia will not only promote the timely establishment of the etiological factor of this condition and adequate treatment of the underlying disease, but also improve the quality and sometimes save the patient’s life.